Delay-Dependent Impairments in Memory and Motor Functions After Acute Methadone Overdose in Rats - Ahmad-Molaei, Leila; Hassanian-Moghaddam, Hossein; Farnaghi, Fariba; Tomaz, Carlos; Haghparast, Abbas (Frontiers in Pharmacology, 2018)
Methadone is used as a substitution drug for the treatment of opioid dependence and chronic pain. Despite its widespread use and availability, there is serious concern with respect to the relatively safety of methadone. The purpose of this study was to characterize how acute methadone overdose affects the cognitive and motor performance of naïve healthy rats. The methadone overdose was induced by administering an acute toxic dose of methadone (15 mg/kg; ip; equivalent dose of 80% of LD50) to adolescent rats. Resuscitation using a ventilator pump along with a single dose of naloxone (2 mg/kg; ip) was administered following the occurrence of apnea. The animals which were successfully resuscitated were divided randomly into three apnea groups that were evaluated either on day 1, 5 or 10 post-resuscitation (M/N-Day 1, M/N-Day 5 and M/N-Day 10 groups) in the Y-maze and novel object memory recognition tasks as well as pole and rotarod tests. The data revealed that a single toxic dose of methadone had adverse effect on spontaneous behavior. In addition, Recognition memory impairment was observed in the M/N-Day 1, 5 and 10 groups after methadone-induced apnea. Further, descending time in the M/N-Day 5 group increased significantly in comparison with its respective Saline control group. The overall results indicate that acute methadone-overdose-induced apnea produced delay-dependent cognitive and motor impairment. We suggest that methadone poisoning should be considered as a possible cause of delayed neurological disorders, which might be transient, in some types of memory or motor performance in naïve healthy rats.